International evaluation of circumferential resection margins after rectal cancer resection: insights from the Swedish and Dutch audits. (27th November 2019) - Detering, R.; Saraste, D.; de Neree tot Babberich, M. P. M.; Dekker, J. W. T.; Wouters, M. W. J. M.; van Geloven, A. A. W.; Bemelman, W. A.; Tanis, P. J.; Martling, A.; Westerterp, M.; ,
Abstract: Aim: This study aimed to determine predictive factors for the circumferential resection margin (CRM) within two northern European countries with supposed similarity in providing rectal cancer care. Method: Data for all patients undergoing rectal resection for clinical tumour node metastasis (TNM) stage I–III rectal cancer were extracted from the Swedish ColoRectal Cancer Registry and the Dutch ColoRectal Audit (2011–2015). Separate analyses were performed for cT1–3 and cT4 stage. Predictive factors for the CRM were determined using univariable and multivariable logistic regression analyses. Results: A total of 6444 Swedish and 12 089 Dutch patients were analysed. Over time the number of hospitals treating rectal cancer decreased from 52 to 42 in Sweden, and 82 to 79 in the Netherlands. In the Swedish population, proportions of cT4 stage (17% vs 8%), multivisceral resection (14% vs 7%) and abdominoperineal excision (APR) (37% vs 31%) were higher. The overall proportion of patients with a positive CRM (CRM+) was 7.8% in Sweden and 5.4% in the Netherlands. In both populations with cT1–3 stage disease, common independent risk factors for CRM+ were cT3, APR and multivisceral resection. No common risk factors for CRM+ in cT4 stage disease were found. An independent impact of hospital volume on CRM+ could be demonstrated for the cT1–3 Dutch population. Conclusion: Within two northern European countries with implemented clinical auditing, rectal cancer care might potentially be improved by further optimizing the treatment of distal and locally advanced rectal cancer.